Panorama de la educación inclusiva en Ecuador - Aguas Calderón, Jefferson Andrés (2019)
The following journalistic research explains the current panorama of inclusive education in Ecuador. Taking into account the processes and projects aimed at trying to generate inclusive practices towards people with disabilities in this area. It is essential to know the current state through a contextualized comparison of inclusive education in the country. It is of fundamental importance that the actors responsible for the realization of an inclusive work are sensitized and have a complete understanding of the subject in order to be an example and to promote a free acceptance of the "normal" people to the people with disabilities. Ecuador, since 2018, has been working specifically for inclusion. First, it has resulted in a Management and Care Model for people with special education needs associated with disabilities. As a complement and to achieve a quality education, an agreement was made in which about 11.400 teachers would be part of the “Training Program of Inclusive Education and Sustainable Learning.” Currently, the training of 5,500 teachers in the coastal region was completed and this year, the program will continue with the mountain and Amazonian as well. It is worth mentioning that this research takes into account the qualitative methodology and interviews as the main techniques. Also, its relevant sources are experts in education, parents, and people of priority care.